Pembangunan Aplikasi Pelaporan Informasi Jalan Rusak di Kota Malang - Abyan Naufal Amanullah Sugiharto; Faizatul Amalia; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Road as an infrastructure for transportation can be damaged by various causes. Dinas Pekerjaan Umum dan Penataan Ruang (DPUPR) is a regional autonomy in infrastructure which covers road. Community complains damaged roads via government's online complaint website due to DPUPR's absence of own platform. This research develops an application which accomodates complains from community regarding damaged roads, the complaints are then received by DPUPR first hand. The application is developed using Waterfall System Development Life Cycle consisting of literature study, requirement analysis, design, implementation, testing, conclusions and suggestions. The results from this research are 13 functional requirements and two non-functional requirements involving three actors on requirement analysis, these requirements generate design and implementation i.e. architecture design, component design, data design and interface design, and implements code, data and interface. The results of implementation are tested with validation testing using Blackbox testing with three test cases resulted 100% validity and unit testing using Whitebox testing with three samples resulted 100% validity, usability testing is conducted with System Usability Scale involving six respondents which resulted score of 75.25, compatibility testing is conducted using Firebase Test Lab which resulted that the application can be run on five different devices with different API levels.